Expectations and disadvantages: a case study approach exploring the mental health challenges of elite, student-athlete women - Wilkins, L.; Benallal, N.; Allen, P. M.; Beukes, E.; Healy, L. C. (International Journal of Sport and Exercise Psychology, 2025)
Elite athletes, student-athletes, and women are reported to have an increased risk of experiencing mental health concerns, yet little is known about how the intersectionality of these three factors affect the individual. The present study addressed this by interviewing members of an international women`s Junior World Cup hockey team. Reflexive thematic analysis was used to identify two triadic themes (i.e., challenges encompassing all three factors) and three dyadic themes (two of the three factors). These findings, and in particular, the triadic themes of "Pressure of Expectation" and "Comparative Disadvantages", reveal the multifaceted nature of the challenges faced by this unique cohort. We identify possible explanations for our findings and discuss implications for optimising the experiences of elite, student-athlete women.